2017
DOI: 10.1161/circulationaha.116.026075
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Cardiac Death in Patients With Ischemic Heart Failure Undergoing Coronary Artery Bypass Grafting

Abstract: Background The risk of sudden cardiac death (SCD) in patients with heart failure following CABG has not been examined in a contemporary clinical trial of surgical revascularization. This analysis describes the incidence, timing and clinical predictors of SCD after CABG. Methods Patients enrolled in the Surgical Treatment of Ischemic Heart Failure (STICH) trial who underwent CABG with or without surgical ventricular reconstruction (SVR) were included. We excluded patients with prior ICD and those randomized o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 25 publications
4
12
0
Order By: Relevance
“…Our results build on a previous analysis of SCD from the STICH trial by Rao et al [26]. Analyzing all 1,411 patients who underwent CABG across the STICH trial, Rao et al observed 113 occurrences of SCD over 5 years for an 8.5% 5-year cumulative incidence of SCD [26]. Notably, SCD risk was greatest in the postoperative window from 30-90 days.…”
Section: Plos Onesupporting
confidence: 79%
See 2 more Smart Citations
“…Our results build on a previous analysis of SCD from the STICH trial by Rao et al [26]. Analyzing all 1,411 patients who underwent CABG across the STICH trial, Rao et al observed 113 occurrences of SCD over 5 years for an 8.5% 5-year cumulative incidence of SCD [26]. Notably, SCD risk was greatest in the postoperative window from 30-90 days.…”
Section: Plos Onesupporting
confidence: 79%
“…Previous studies have shown that improvement in LVEF is associated with reduced risk of SCD [23][24][25]. Our results build on a previous analysis of SCD from the STICH trial by Rao et al [26]. Analyzing all 1,411 patients who underwent CABG across the STICH trial, Rao et al observed 113 occurrences of SCD over 5 years for an 8.5% 5-year cumulative incidence of SCD [26].…”
Section: Plos Onesupporting
confidence: 76%
See 1 more Smart Citation
“…Third, although there have been considerable advancements in the mode and care of coronary revascularization since the era of secondary prevention randomized trials, contemporary mode-of-death analyses continue to identify sudden death as a common mechanism of cardiovascular death in patients undergoing percutaneous 77 and surgical revascularization. 78 Future efforts are needed to further refine arrhythmic risk evaluation in secondary prevention patients with ischemic heart disease. Specific populations of interest include those with residual coronary disease and/or ischemia after “culprit lesion” revascularization.…”
Section: Systems Of Care For Secondary Prevention Patients and Opportunities For The Futurementioning
confidence: 99%
“…The recently published results from the Sudden Cardiac Death in Patients With Ischemic Heart Failure Undergoing Coronary Artery Bypass Grafting (STICH) trial indicate that the monthly risk of SCD shortly after CABG among patients with a low LVEF is the highest between the first and the third month. In such patients, especially those with an increased perioperative end-systolic volume index and/or B-type natriuretic peptide, the risk stratification for SCD should occur early in the postoperative period [36].…”
Section: Treatment Of Electrical Stormmentioning
confidence: 99%